In vivo periodontal tissue regeneration by periodontal ligament stem cells and endothelial cells in three‐dimensional cell sheet constructs. (6th August 2016) - Panduwawala, C. P.; Zhan, X.; Dissanayaka, W. L.; Samaranayake, L. P.; Jin, L.; Zhang, C.
Abstract : Background and Objective: Chronic periodontitis causes damage to tooth‐supporting tissues, resulting in tooth loss in adults. Recently, cell‐sheet‐based approaches have been studied to overcome the limitations of conventional cytotherapeutic procedures for periodontal regeneration. The purpose of the present study was to investigate the regenerative potential of periodontal ligament stem cells (PDLSCs) and human umbilical vein endothelial cells (HUVECs) in three‐dimensional (3D) cell sheet constructs for periodontal regeneration in vivo . Material and Methods: PDLSCs, HUVECs or co‐cultures of both cells were seeded onto temperature‐responsive culture dishes, and intact cell sheets were fabricated. Cell sheets were wrapped around the prepared human roots in three different combinations and implanted subcutaneously into immunodeficient mice. Results: Histological evaluation revealed that after 2, 4 and 8 wk of implantation, periodontal ligament‐like tissue arrangements were observed around the implanted roots in experimental groups compared with controls. Vascular lumens were also observed in periodontal compartments of HUVEC‐containing groups. Periodontal ligament regeneration, cementogenesis and osteogenesis were evident in the experimental groups at both weeks 4 and 8, as shown by immunostaining for periostin and bone sialoprotein. Human cells in the transplanted cell sheets were stained by immunohistochemistry for the presence of human mitochondria. Conclusions: The 3D cell sheet‐based approach may be potentially beneficial and is thus encouraged for future regenerative periodontal therapy.